“ONTOLOGICAL SCANDAL”: GAMES WITH BOUNDARIES BETWEEN WORLDS AND TEXTS - Dimova, Marija Gjorgjieva (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
Starting from the theoretical premises for the ontological dominant of postmodern prose, this text interprets these premises in the novel The Symmetry Teacher by Russian author Andrei Bitov. The interpretation is focused on two levels: first, interpretation of ontological themes and metafictional devices through which these themes are articulated in the Bitov’s novel; secondly, the function of those themes and devices, regarding the illustration of ontological games with the boundaries between the worlds (literature-reality, art-life, fiction-fact), between texts (original and translated texts and meta-texts) and between genres.